(untitled) (Journal of Forensic Medicine & Toxicology, 2019)
World Health Organization (WHO) has aptly recognized snake envenomation as a neglected tropical disease because it is a medical emergency in tropical regions. But beyond that it is also a fairly ignored medico legal scourge, particularly in India. Being an accidental unnatural death, a fatal snake envenomation usually invites an inquest. The forensic science laboratories (FSLs) are required to perform a chemical analysis of post-mortem exhibits of unfortunate victims and to conclusively report the likelihood of snake envenomation. The positive chemical reports confirming the snake envenomation will be required for ascertaining the cause of death and thereby advocating the disbursement of insurance money. In this study, we collected the data on status of snake venom analysis in FSLs of India. State sponsored welfare schemes providing the financial assistant to victims of snake envenomation of Haryana state of India were also identified and their data on disbursal of insurance money to families of fatal snake envenomation victims was enquired. The data from Indian FSLs suggests the lack of standard protocol for venom analysis from post-mortem samples. Most laboratories don’t perform such analysis due to lack of facilities. Enquiries from state authorities revealed that in many cases the insurance money could not be disbursed to families of fatal snake envenomation victims due to lack of confirmatory reports from FSLs.